Training loads and intensities: Impact on performance in amateur rugby players - Enric Conesa-Milian; Carme Jové-Deltell; Vicenç Hernández-González; Saül Aixa-Requena; Teresa Fonseca; Joaquim Reverter-Masia (Motricidade)
The article addresses the physical demands of amateur rugby, using global positioning system technology to analyze player performance during matches and training sessions. The results show that matches are more physically demanding than training, with greater distances covered, more sprints, and a higher number of impacts. However, training sessions adequately replicate accelerations and decelerations, although there are fewer physical contacts to avoid injuries. Additionally, an improvement in players’ aerobic capacity was observed after five weeks of training, highlighting the need to personalize training sessions to optimize individual performance.